An application of the regression analysis to explain the coach change on team performance in soccer - C. Lago (Asociación Española de Ciencias del Deporte, 2010)
In this paper, the impact of the coach´s change on the results obtained by teams in the Spanish Soccer League is analyzed. The empirical analysis is based on data from the 1997-1998 to the 2006-2007 seasons of the First and Second Spanish Soccer League. According to the estimations based on linear regression analysis and mean comparison test, the first conclusion is that teams with a new coach obtain more points in comparison with the results reached by the dismissed coach. Moreover, it has been verified that the winning effect of the new coach does not have a linear influence throughout the time. The positive effect of the coach's change on the result of teams diminishes progressively up to managing to be annulled. In other words, the higher the number of days the lower the impact of the winning effect of the new coaches. Finally, it has been verified that the effect of the coach´s change on the results of teams is not different when there are compared the First one and the Second Division of the Spanish Soccer League. Key Words:coach´s change, soccer, linear regression analysis, results.